Displacement of the positions obtained with the PPP – IBGE caused by changes in transformation parameters between IGb08 and SIRGAS2000 (Research, Society and Development, 2022)
In this work we have investigated the displacement in coordinates processed by the PPP-IBGE before 17/05/2020, when the IBGE adopted new transformation parameters between IGb08 and SIRGAS2000. The parameters Applied until the former date considered 3 translations, 1 scale fator and 3 rotations between both geodetic reference systems. The parameters adopted after 15/05/2020 not only show slightly diferences in translations but also adopted null rotations, that is, both systems were considered to be parallel. For demonstration purpose, we used data processed by the PPP-IBGE in 2016, before the change in parameters. The coordinates converted from IGb08 to SIRGAS2000 using both set of parameters were calculated and compared, and the resulting displacement was ~ 3 cm, as expected by the IBGE. Therefore, in all those cases in which the precision has not to be better than 3 cm the change in parameters can be neglected.